Pemberdayaan Masyarakat Miskin Melalui Program Padat Karya di Kecamatan Wonocolo Kota Surabaya - Nabiilah Haniifah Azizah; Muhammad Agus Muljanto (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
In order to reduce poverty rates, the Surabaya City Government has enacted Surabaya Mayor Regulation Number 83 of 2023 concerning the Labor-Intensive Program. Wonocolo sub-district has become one of the areas implementing this program through the inauguration of the Labor Intensive House, which encompasses various businesses. This research aims to describe and analyze community empowerment through labor-intensive programs in Wonocolo District to business sustainability using the (Suharto, 2014) 5P theory according to : Enabling, Strengthening, Protecting, Supporting, and Maintaining. This research uses descriptive qualitative research methods with purposive sampling techniques for informant selection. The results of the study indicate that: (1) Enabling has been carried out through socialization activities, interest data collection, training, and guidance. However, motivation has not fully raised awareness among business actors. (2) Strengthening is progressing well through training, but a lack of in-depth understanding. (3) Protection through market access has been implemented through marketing activities, but it is not uniform across all labor-intensive business types. (4) Support in the form of assistance has not been conducted intensively for several businesses, so the issues hindering business sustainability remain unresolved. (5) Maintenance is carried out through monitoring and evaluation, but monitoring is not conducted routinely, leading to unresolved issues within this program, which become obstacles to business sustainability. Although this program aligns with the empowerment approach, its implementation has not been optimal, and the objectives of the labor intensive program have not been achieved in Wonocolo District.